Neurobiological perspective of 22q11.2 deletion syndrome. (November 2019) - Zinkstok, Janneke R; Boot, Erik; Bassett, Anne S; Hiroi, Noboru; Butcher, Nancy J; Vingerhoets, Claudia; Vorstman, Jacob A S; van Amelsvoort, Therese A M J
Summary: 22q11.2 deletion syndrome is characterised by a well defined microdeletion that is associated with a high risk of neuropsychiatric disorders, including intellectual disability, schizophrenia, attention-deficit hyperactivity disorder, autism spectrum disorder, anxiety disorders, seizures and epilepsy, and early-onset Parkinson's disease. Preclinical and clinical data reveal substantial variability of the neuropsychiatric phenotype despite the shared underlying deletion in this genetic model. Factors that might explain this variability include genetic background effects, additional rare pathogenic variants, and potential regulatory functions of some genes in the 22q11.2 deletion region. These factors might also be relevant to the pathophysiology of these neuropsychiatric disorders in the general population. We review studies that might provide insight into pathophysiological mechanisms underlying the expression of neuropsychiatric disorders in 22q11.2 deletion syndrome, and potential implications for these common disorders in the general (non-deleted) population. The recurrent hemizygous 22q11.2 deletion, associated with 22q11.2 deletion syndrome, has attracted attention as a genetic model for common neuropsychiatric disorders because of its association with substantially increased risk of such disorders. 1 Studying such a model has many advantages. First, 22q11.2 deletion has been genetically well characterised. 2 Second, most genes present in the region typically deleted at the 22q11.2 locus are expressed in the brain. 3–5 Third, genetic diagnosis might be made early in life, long before recognisable neuropsychiatric disorders have emerged. Thus, this genetic condition offers a unique opportunity for early intervention, and monitoring individuals with 22q11.2 deletion syndrome throughout life could provide important information on factors contributing to disease risk and protection. Despite the commonly deleted region being shared by about 90% of individuals with 22q11.2 deletion syndrome, neuropsychiatric outcomes are highly variable between individuals and across the lifespan. A clear link remains to be established between genotype and phenotype. 3, 5 In this Review, we summarise preclinical and clinical studies investigating biological mechanisms in 22q11.2 deletion syndrome, with a focus on those that might provide insight into mechanisms underlying neuropsychiatric disorders in 22q11.2 deletion syndrome and in the general population.